Incidences of Obstetric Outcomes and Sample Size Calculations: A Danish National Registry Study Based on All Deliveries From 2008 to 2015. Issue 4 (December 2020) - Hoegh, S.; Thellesen, L.; Christensen, K.B.; Bergholt, T.; Hedegaard, M.; Sorensen, J.L.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:34–41) As adverse obstetric outcomes become less frequent in high-income countries, the ability to demonstrate significant effects of new interventions becomes more challenging. This is because many study designs do not have adequate statistical power to validate rare outcomes attributed to a specific intervention. The aim of this study was to report the incidence of relevant obstetric outcomes from existing literature and based on this data, to calculate sample sizes needed for tentative future randomized clinical trials (RCTs) to ensure the quality of scientific findings.